Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages man, woman and child must be brought to realise that, even under the far from satisfactory social conditions of capitalist society, there is much that each of us can do to maintain health and fighting fitness. We must go forward to a vast extension of health work as a means not only for the improvement of social conditions and vital services in our national life, but as a means through which we may make yet further contributions to increased production and the establishment and maintenance of a Second Front for the achievement of Victory. APPENDIX* THE HEALTH SERVICES The Health Services of the country fall into two major categories:— (a) Mainly preventive. (b) Partly preventive and mainly curative. Category (a) covers such things as ensuring adequate and pure water supply ; refuse and sewage collection ; food inspection ; overcrowding ; port health (ship's passengers and food) ; factory inspection ; vaccination and immunisation ; notification of infectious diseases, etc. The workers employed in this section of the services, e.g. food and sanitary inspectors, administrative officers and clerks in the public health department, social workers and so on, are not numerous and are largely non-institutional. Category (b) includes all hospital and health centres, maternity homes, child and infant welfare clinics, T.B. dispensaries and similar institutions and domiciliary services provided by general practitioners, district nurses and the National Health Insurance Scheme, etc. The numerous workers employed in these services are chiefly doctors, dentists, nurses, almoners, pharmacists, radiographers, masseuses, laboratory technicians, administrators, male and female domestics, maintenance staff and so on. They are largely institutional workers and the majority reside at their place of work. It is with the latter category that the following survey is principally concerned. 1. ADMINISTRATION Before we consider services and personnel a note must be made regarding the of the health services. The Ministry of Health (which was formed only in 1919) is by no means the sole administrative body responsible for the nation's health ; there is a vast complexity of other bodies and authorities, e.g.: — Statutory Bodies Ministry of Education — School Medical Service. Home Office — Factory inspection and Industrial Health. Mines Department (Board of Trade) — Medical inspection of mines. Board of Control — Mental Health Services. * Figures contained in this Appendix relate almost entirely to England and Wales. 28 15X/2/103/252